Penambatan Molekul Senyawa Aktif Spirulina platensis sebagai Inhibitor TMPRSS2 untuk Mencegah Infeksi SARS-COV-2: Molecular Docking of Active Compound of Spirulina platensis as TMPRSS2 Inhibitor to Prevent the SARS-COV-2 Infection - Putu Kristiani Kalontong; Mega Safithri; Kustiariyah Tarman (Jurnal Pengolahan Hasil Perikanan Indonesia, 2022)
Spirulina platensis is a blue green algae (Cyanophyta) species that consumed as a healthy food and as a source of various types of nutritions that needed by the human body. The compounds that isolated from the microalgae has been reported as effective inhibitors against several types of viruses. COVID-19 is a disease that caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In mechanism, spike protein SARS-CoV-2 is activated by TMPRSS2 to enter host cells. Thus, inhibiting TMPRSS2 activity can be prevent the SARS-COV-2 infection. This study aims to analyze the potential of the active compound of the extracts of S. platensis as TMPRSS2 inhibitor to prevent the SARS-COV-2 infection that expected to reduce the severity of the COVID-19. This study using molecular docking study based on the affinity energy (ΔG) and inhibition constant (Ki). The potential active compound also compared to natural ligands and nafamostat. Molecular docking was conducted on 45 of 108 active compounds of S. platensis with TMPRSS2 protein. Molecular docking results indicate that quercitrin has the potential as a TMPRSS2 inhibitor due to its most negative ΔG by -7.40 kcal/mol and inhibition constant by 3.77 M. The quercitrin also can bind to 2 residues from the active side of TMPRSS2 than natural ligands and nafamostat that only bind to 1 residue of the active side of TMPRSS2.